Developing Islamic finance in fragile states - Hassan, Rusni; Haron, Abdullah; Benaicha, Mohamad (Ssskr Innani Mahavidyalaya.karanja, 2021)
This exploratory paper is an inquiry into the problem of how to go about developing Islamic finance in fragile states. A qualitative analysis was conducted regarding the context in which Islamic financial intermediaries currently operate. The first finding is that an unconventional look has to be taken at the nature of fragility. This paper proposes looking beyond the impediment of failed political institutions and into the possibilities available to the private and third sectors, as well as a possible cooperative approach between IFIs and fragile state governments. Several unique approaches cater to various challenges that recur in fragile states including targeting the private and third sectors when political institutions lack reliability, getting around absorptive capacity constraints using Islamic microfinance, increasing financial participation through microfinance products and mobile services and enticing cooperation of governments through financing development. The existing challenges could also be turned into opportunities ifs framed properly. The opportunity exists for the Islamic finance infrastructure to aid Islamic financial intermediaries in expanding to fragile state markets, to develop the financial sector in such markets and in turn formalize the economy.The lack of development in fragile states allows their authorities as well as Islamic financial intermarries to leverage the opportunity presented by technology. Digital finance allows for greater inclusion and instills greater confidence in consumers due to the transparency and ease of access provided by technology.